Effect of the metals iron, copper and silver on fluorobenzene biodegradation by Labrys portucalensis - Moreira, Irina S. (2013)
Organic and metallic pollutants are ubiquitous in the environment. Many metals are reported to be toxic to microorganisms and to inhibit biodegradation. The effect of the metals iron, copper and silver on the metabolism of Labrys portucalensis F11 and on fluorobenzene (FB) biodegradation was examined. The results indicate that the addition of 1 mM of Fe2+ to the culture medium has a positive effect on bacterial growth and has no impact in the biodegradation of 1 and 2 mM of FB. The presence of 1 mM of Cu2+ was found to strongly inhibit the growth of F11 cultures and to reduce the biodegradation of 1 and 2 mM of FB to ca. 50 %, with 80 % of stoichiometrically expected fluoride released. In the experiments with resting cells, the FB degraded (from 2 mM supplied) was reduced ca. 20 % whereas the fluoride released was reduced to 45 % of that stoichiometrically expected. Ag+ was the most potent inhibitor of FB degradation. In experiments with growing cells, the addition of 1 mM of Ag+ to the culture medium containing 1 and 2 mM of FB resulted in no fluoride release, whereas FB degradation was only one third of that observed in control cultures. In the experiments with resting cells, the addition of Ag+ resulted in 25 % reduction in substrate degradation and fluoride release was only 20 % of that stoichiometrically expected. The accumulation of catechol and 4-fluorocatechol in cultures supplemented with Cu2+ or Ag+ suggest inhibition of the key enzyme of FB metabolism-catechol 1,2-dioxygenase.